Improvement of Millennial Generation Mental Health Due to Pandemic Effects - Silfania Oktaviani; Rizki Yanti Shalsabilla; Fenny Nurhalyza; Charli Sitinjak (Journal of Social Science, 2023)
The millennial generation is a generation born in the range of 1980 to 2000. Known as millennials because this generation is developing in technological advances and the digital era. This decade is a moment that dominates the millennial generation. The role of the millennial generation in the present generation has a great influence on the progress of the nation. The mindset that tends to be at the peak of development encourages this generation to become the pioneers of the movement for change. However, in the midst of the peak of its development, the millennial generation must face a pandemic that affects the whole world. The purpose of this study is to determine the improvement of Millennial Generation Mental Health Due to the Effects of the Pandemic. This research applies a method of systematic review in which secondary data collection is carried out, and is a synthesis of all available relevant evidence that brings together all existing primary studies for review. The pandemic caused by coronavirus disease 2019 (COVID -19) caused the cessation of many activities throughout the world. This pandemic period has a significant negative impact both in the fields of education, economy, and health. In addition to the increasing number of suspects and deaths caused by covid-19, mental health also occupies an important role as an influence caused by the pandemic. The productive times of the millennial generation must be faced with the pandemic as the biggest challenge. Moreover, as many as 27% of millennials are negatively affected by mental health due to COVID-19. Some of these disorders include fear of contracting it, stress due to work, anxiety, fear, and depression to face the future.